Hermite–Hadamard-Type Inequalities for Generalized Convex Functions via the Caputo-Fabrizio Fractional Integral Operator - Dong Zhang (Hindawi Limited, 2021)
Due to applications in almost every area of mathematics, the theory of convex and nonconvex functions becomes a hot area of research for many mathematicians. In the present research, we generalize the Hermite–Hadamard-type inequalities for p,h-convex functions. Moreover, we establish some new inequalities via the Caputo-Fabrizio fractional integral operator for p,h-convex functions. Finally, the applications of our main findings are also given.